2021
DOI: 10.1136/bmjpo-2021-001209
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences—household stressors and children’s mental health: a single centre retrospective review

Abstract: ObjectiveTo determine the prevalence of reported ‘household stressor’ adverse childhood experiences (ACEs) in families of children presenting with neurodevelopmental, behavioural or emotional difficulties and to determine whether family vulnerabilities, individually or cumulatively, were associated with particular clinical symptomatology.DesignRetrospective chart review followed by statistical analysis of family stressors and clinical symptomatology.SettingA community paediatric clinic in Australia.Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Stressful childhood events such as ACEs have been shown to increase the possibility of the development of ADHD and increase the severity of symptoms. Four studies (Bauer et al, 2022; Bomysoad & Francis, 2020; Holmes et al, 2021; Jimenez et al, 2017; Zarei et al, 2021) demonstrate that stress which is specifically experienced within households is indicative of higher incidences of ADHD in children. Trauma was associated with, at age 11 years, ADHD and hyperactivity disorders (1·47 [1·01‐2·13]) (Bauer et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Stressful childhood events such as ACEs have been shown to increase the possibility of the development of ADHD and increase the severity of symptoms. Four studies (Bauer et al, 2022; Bomysoad & Francis, 2020; Holmes et al, 2021; Jimenez et al, 2017; Zarei et al, 2021) demonstrate that stress which is specifically experienced within households is indicative of higher incidences of ADHD in children. Trauma was associated with, at age 11 years, ADHD and hyperactivity disorders (1·47 [1·01‐2·13]) (Bauer et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Trauma was associated with, at age 11 years, ADHD and hyperactivity disorders (1·47 [1·01‐2·13]) (Bauer et al, 2022). A study (Holmes et al, 2021) found that 60.7% of children presenting with ADHD had experienced one or more household stressor ACEs. A positive odds‐ratio (OR) > 1.0 association implied the presence of co‐occurring ACEs, thus, all five household stressor ACEs were positively associated with each other (Holmes et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations